2009
DOI: 10.1083/jcb.200904161
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila deoxyhypusine hydroxylase homologue nero and its target eIF5A are required for cell growth and the regulation of autophagy

Abstract: Hypusination is a unique posttranslational modification by which lysine is transformed into the atypical amino acid hypusine. eIF5A (eukaryotic initiation factor 5A) is the only known protein to contain hypusine. In this study, we describe the identification and characterization of nero, the Drosophila melanogaster deoxyhypusine hydroxylase (DOHH) homologue. nero mutations affect cell and organ size, bromodeoxyuridine incorporation, and autophagy. Knockdown of the hypusination target eIF5A via RNA interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 56 publications
1
57
0
1
Order By: Relevance
“…In contrast, this enzyme is required for development of multicellular eukaryotes, e.g. C. elegans [54], D. melanogaster [55] and mouse [56]. Considering the stringency in the requirement for the hypusinated form of eIF5A in higher organisms, it is tempting to speculate that eIF5A and its hypusine modification pathway have evolved along with the increase in polyproline-containing proteins with critical functions in higher eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this enzyme is required for development of multicellular eukaryotes, e.g. C. elegans [54], D. melanogaster [55] and mouse [56]. Considering the stringency in the requirement for the hypusinated form of eIF5A in higher organisms, it is tempting to speculate that eIF5A and its hypusine modification pathway have evolved along with the increase in polyproline-containing proteins with critical functions in higher eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…DOHH contains 2 molecules of iron, thought to be present in a diiron active site, per enzyme (Kim et al, 2006), and mutation of the conserved His-Glu motifs impaired Fe and/or eIF5A binding to DOHH (Kang et al, 2007). In contrast to the non-essential nature of DOHH in budding and fission yeast (Park et al, 2006; Weir and Yaffe, 2004), loss of DOHH was recessively lethal in C. elegans (Sievert et al, 2014; Sugimoto, 2004), Drosophila (Patel et al, 2009), and mouse (Sievert et al, 2014), suggesting perhaps that the hydroxyl group on hypusine is more critical for eIF5A function in metazoan cells. While the function of the hydroxyl group on hypusine is unknown, it is noteworthy that the yield of hypusinated eIF5A in bacteria co-expressing eIF5A, DHS and DOHH is greater than the yield of deoxyhypusinated eIF5A in bacteria co-expressing eIF5A and DHS (Park et al, 2011).…”
Section: Post-translational Modification Of Eif5a and Ef-pmentioning
confidence: 97%
“…Interestingly, polysome analyses in Drosophila and mammalian cells likewise indicated a role for eIF5A in translation elongation. Knockdown of eIF5A expression in Drosophila S2 cells resulted in the accumulation of polysomes (Patel et al, 2009), and whereas treatment of mammalian cells with arsenite caused impaired translation initiation and polysome loss, knockdown of eIF5A was reported to block this disassembly of polysomes in arsenite-treated cells (Li et al, 2010). In further support of the notion that loss or inactivation of eIF5A impairs translation elongation, two studies reported that eIF5A mutations cause an increase in the average ribosomal transit time, as measured by the time it takes for a ribosome following initiation to synthesize and release a completed polypeptide (Saini et al, 2009; Gregio et al, 2009).…”
Section: Yeast Studies Reveal a Role For Eif5a In Translation Elongationmentioning
confidence: 99%
“…The absence of DOHH is lethal to Caenorhabditis elegans and Drosophila melanogaster [173][174][175]. Additionally, in mice the homozygous deletion of eIF5A-1 or DHPS has shown to be unviable [176].…”
Section: Polyamines In Cell Proliferationmentioning
confidence: 97%